Carbon fiber reinforced composite material structure simulation debonding defect thermal resistance equivalent test piece and preparation method thereof
By using carbon fiber braided fabric, thermal resistance material and cured resin, combined with vacuum flow diversion molding method, the problem of inaccurate simulation of defragment defects in the prior art is solved, and the realization of thermal wave transmission is achieved High accuracy of simulation and infrared thermal imaging detection.
Patent Information
- Application Number
- CN202510018637.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to effectively simulate debonding defects in carbon fiber reinforced composite materials, resulting in thermal wave transfer not meeting the real situation, affecting the accuracy of infrared thermal imaging detection.
Thermal resistance equivalent test pieces that simulate defragmentation defects are prepared using carbon fiber woven fabric, thermal resistance materials and cured resins. Thermal resistance equivalent specimens are made by vacuum flow molding to ensure that the thermal resistance material is flush with the carbon fiber woven fabric in the defect space, and simulate the real Discharge defect.
The heat wave transmission flow direction is closer to the real situation, the accuracy of infrared thermal imaging detection is improved, and the preparation method is simple and low cost, and it is suitable for implementation under ordinary laboratory conditions.
Smart Images

Figure CN119413847A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an equivalent test piece for simulating defects, which is applied to defect detection and evaluation of carbon fiber reinforced composite materials. The invention also relates to a preparation method of the equivalent test piece. Background Art
[0002] Carbon fiber reinforced composite (CFRP) is a composite material composed of anisotropic carbon fiber and matrix. It is widely used in important engineering fields such as wind turbine blades, helicopter rotors, drone shells, high-pressure pipelines and medical devices because of its light weight, high specific strength, high specific modulus, corrosion resistance, low thermal expansion and excellent fatigue resistance. However, the manufacturing process of carbon fiber reinforced composites is complicated, and defects at any stage may affect the final performance. During use, these tiny defects may expand under the action of external loads, leading to problems such as debonding, greatly reducing the structural strength of the material, and may even cause serious engineering safety accidents. Therefore, timely identification and evaluation of these potential faults during the life cycle of carbon fiber reinforced composites can effectively reduce safety hazards and reduce maintenance costs. Therefore, it is very necessary to use appropriate non-destructive non-contact detection technology to detect debonding defects in carbon fiber reinforced composite structures. Active infrared thermal imaging technology actively applies controllable thermal excitation to the test piece. When there is damage on the surface or inside of the test piece, the thermal conductivity here will change, which will cause temperature differences on the surface of the test piece, resulting in local hot or cold areas. The surface temperature of the test piece is recorded by an infrared thermal imager, and the thermal image sequence obtained by analysis and processing is used to achieve qualitative and quantitative characterization of surface or internal defects of the object. The visualization, intuitive detection effect and single large-area detection of infrared thermal imaging technology make it have a wide range of application prospects.
[0003] At the same time, the debonding defect is equivalent to the internal defect space being filled with air. Since the thermal conductivity of the layered defect space is different from that of the normal area, it is very intuitive and reliable to observe the abnormal thermal conduction by thermally exciting the sample and reflecting the damage defects of the carbon fiber reinforced composite material. Since there is no better method to prepare simulated debonding defects in carbon fiber reinforced composite structure specimens, most of them simulate the debonding defects under the surface of the material by processing flat-bottom holes on the back, or fill the back gap with the processed carbon fiber cylinder after placing the film thermal resistance material in the blind hole processed on the back. These methods are used to replace the real debonding defects inside the fiber layer. The debonding defects prepared by these methods have obvious differences in geometric shape and thermal conductivity from the real defects. This difference will cause a large temperature difference (changing the transmission flow direction of the heat wave in the specimen, and to a certain extent affecting the infrared thermal wave non-destructive testing test results of simulated debonding defects of carbon fiber reinforced composite structures), and it does not conform to the actual engineering situation. The experimental results obtained with such specimens may not be sufficient to guide actual production testing. Summary of the invention
[0004] The first technical problem to be solved by the present invention is to provide a carbon fiber reinforced composite material structure simulating debonding defect thermal resistance equivalent test piece in which the transmission direction of heat waves in the test piece is closer to the actual situation in view of the above-mentioned technical status quo.
[0005] The second technical problem to be solved by the present invention is to provide a method for preparing a thermal resistance equivalent specimen of a carbon fiber reinforced composite material structure simulating debonding defects in which the transmission direction of heat waves in the specimen is closer to the actual situation.
[0006] The third technical problem to be solved by the present invention is to provide a method for preparing a thermal resistance equivalent test piece of a carbon fiber reinforced composite material structure simulating debonding defects, which is simple to manufacture and low in cost.
[0007] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: a carbon fiber reinforced composite material structure simulated debonding defect thermal resistance equivalent test piece, characterized in that it includes a carbon fiber woven cloth, a thermal resistance material and a cured resin; the aforementioned carbon fiber woven cloth is a plurality of pieces and is stacked as a whole, and a defect space of a set shape is reserved in the middle of one of the carbon fiber woven cloths in the middle layer; the thermal resistance material is filled in the defect space and kept flush with the upper and lower surfaces of the carbon fiber woven cloth, and the aforementioned cured resin is evenly immersed in the carbon fiber filaments of the carbon fiber woven cloth.
[0008] The technical solution adopted by the present invention to solve the second and third technical problems is: a method for preparing a carbon fiber reinforced composite material structure simulated debonding defect thermal resistance equivalent test piece, characterized in that the preparation method adopts a vacuum infusion molding device, the vacuum infusion molding device includes A resin barrel containing curing resin; A resin collector for collecting excess cured resin; A constant temperature drying oven, with a vacuum bag built in, one end of the vacuum bag is connected to the resin barrel through a resin delivery pipe, and the other end is connected to the resin collector through a resin collection pipe, the resin delivery pipe is provided with a first pipe clamp to control the opening and closing of the resin delivery pipe, and the resin collection pipe is provided with a second pipe clamp to control the opening and closing of the resin collection pipe; and A vacuum pump connected to the vacuum end of the resin collector; The steps include: Apply release agent evenly on the inner surface of the mold; The carbon fiber woven cloth is cut to prepare the required number of layers, and a defect space of a set shape is cut out in the middle of one of the carbon fiber woven cloths in the middle layer as a defect layer; Arrange and stack the prepared carbon fiber woven cloth in a certain way in the mold, use shaping spray glue to preliminarily shape it during stacking, fill the defect space with thermal resistance material, and ensure that the top and bottom of the thermal resistance material are flush with the upper and lower surfaces of the carbon fiber woven cloth respectively; Lay the release cloth and the guide net on the upper surface of the stacked carbon fiber woven cloth in sequence; The vacuum bag film is attached to the edge of the upper surface of the mold with a sealing tape and sealed. After the vacuum bag film is wrapped, a vacuum bag is formed. Two interfaces are reserved on the surface of the vacuum bag film for connecting the resin delivery pipe and the resin collection pipe respectively. Turn on the vacuum pump, the first pipe clamp and the second pipe clamp, the solidified resin enters the mold due to the negative pressure and is evenly immersed in the carbon fiber filaments of the carbon fiber woven cloth, and the excess solidified resin enters the resin collector through the resin collection pipe; Close the first tube clamp and the second tube clamp to maintain the vacuum state in the vacuum bag; The carbon fiber filaments are allowed to stand for a while, and after the solidification of the solidifying resin impregnating the carbon fiber filaments is completed, the carbon fiber filaments are taken out and demoulded to obtain a carbon fiber reinforced composite material structure simulating debonding defect thermal resistance equivalent test piece.
[0009] Preferably, the steps An isolation film is laid between the demoulding cloth and the guide net.
[0010] Preferably, the steps The mold described in the method is made of stainless steel, and the release agent described is an oily release agent.
[0011] Preferably, the steps The shaping spray adhesive described in the method is 3M's Super 77 multi-purpose spray adhesive or GURQI 998 composite material adhesive.
[0012] Preferably, the steps The curing resin described in the invention comprises the following components and their weight ratios: Epoxy resin 98~102: Curing agent 28~32.
[0013] Preferably, the resin collector is provided with a vacuum gauge, and the steps Previously, it also included an airtightness verification step: turn on the vacuum pump for a period of time and then turn it off, and observe the reading of the vacuum gauge to verify the airtightness of the vacuum infusion molding device.
[0014] Preferably, the steps The conditions during the static process are as follows: The constant temperature drying oven was controlled to rise to 70°C at a rate of 2°C / min, and the insulation time was set to 4h. After the epoxy resin impregnating the carbon fiber filaments was cured, they were naturally cooled to 30°C and then removed from the mold.
[0015] Furthermore, the vacuum pump is connected to the air extraction end of the resin collector through a vacuum tube.
[0016] Compared with the prior art, the invention has the advantages that the thermal resistance material is added between the carbon fiber woven cloths to simulate the internal air defects of the real carbon fiber reinforced composite material debonding, so that the thermal resistance equivalent test piece simulating the debonding defect is closer to the real debonding defect in structure, so the test effect is closer to the real value. The results of the internal CT scanning show that the debonding of the invention is consistent with the real situation.
[0017] The position and size of the defect are controlled according to the size and volume of the thermal resistance material and the depth of the filling layer, and carbon fiber reinforced composite materials with different types can be produced by changing the arrangement direction of each layer of carbon fiber woven cloth as needed, and the heat conduction of heat waves in the test piece is similar to the real situation.
[0018] The simplified and improved vacuum infusion molding method used in the present invention is used to make thermal resistance equivalent test pieces simulating debonding defects. Compared with compression molding and autoclave molding, vacuum infusion molding can make carbon fiber reinforced composite parts with complex structures. The required equipment is simple and the cost is low. It can be prepared under ordinary laboratory conditions. Compression molding generally requires steel with high enough strength. It is difficult to make parts with complex structures with such materials. The mold material used in vacuum infusion only needs to withstand vacuum pressure, so the material requirements for the mold are lower than those of compression molding.
[0019] Experiments have shown that the interface thermal resistance equivalent method of the present invention has good effects in the detection of debonding and other types of defects in carbon fiber reinforced composite materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic diagram of the structure of the vacuum infusion molding device in Example 1.
[0021] Figure 2 This is a schematic diagram of the specific structure inside the vacuum bag in Example 1.
[0022] Figure 3 This is a schematic diagram of the structure of the sample after demoulding in Example 1.
[0023] Figure 4 This is a thermal map of the sample surface temperature detected by infrared thermal imaging of the sample in Example 1.
[0024] Figure 5This is a thermal map of the sample surface temperature detected by infrared thermal imaging of the sample in Example 2.
[0025] Figure 6 This is a three-dimensional image of the CT results of the sample in Example 2.
[0026] Figure 7 This is the internal cross-sectional view of the CT results of the sample in Example 2. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below with reference to the accompanying drawings.
[0028] Example 1 (defect depth is about 1.5 mm from the surface): This embodiment is prepared by vacuum infusion molding process. Figure 1 As shown, the vacuum induction molding device includes a resin barrel 1, a resin collector 6, a constant temperature drying oven 2 and a vacuum pump 7. The resin barrel 1 contains solidified resin; the resin collector 6 is used to collect excess solidified resin, and a vacuum gauge 61 is provided on the resin collector 6; a vacuum bag is built into the constant temperature drying oven 2, one end of the vacuum bag is connected to the resin barrel 1 through a resin delivery pipe 4, and the other end is connected to the resin collector 6 through a resin collection pipe 5. The resin delivery pipe 4 is provided with a first pipe clamp 41 to control the on-off of the resin delivery pipe 4, and the resin collection pipe 5 is provided with a second pipe clamp 51 to control the on-off of the resin collection pipe 5; the vacuum pump 7 is connected to the exhaust end of the resin collector 6 through a vacuum pipe 71.
[0029] Use non-woven cloth to dip in appropriate amount of alcohol to wipe the stainless steel mold. The size of the groove in the mold is 100*100*3mm, and a 50mm wide connection surface is left on the upper surface; After the alcohol evaporates, spray the inner surface of the mold evenly with an oily release agent; Cut out 20 pieces of 100*100mm bidirectional woven carbon fiber fabrics of the same size (single layer thickness is about 0.15mm), and cut out a 15*15mm square hole in the center of one of the pieces. Weigh the total weight of the carbon fiber fabric and record it (the weight of the carbon fiber in this experiment is 37.35g); The 20 layers of cut bidirectional woven carbon fiber cloth are placed in the mold in a circular manner according to the arrangement direction of [0°, 45°, -45°, 90°]. Each layer needs to be evenly sprayed with a shaping spray adhesive to shape it. The 11th layer is laid with a carbon fiber cloth with 15*15mm holes cut out, and the thermal resistance material (15*15mm) of the same size and thickness is filled into the defect to ensure that the film is flush with the upper and lower surfaces of the 11th layer of carbon fiber cloth, and the other layers are arranged normally.
[0030] Cut the release cloth, the perforated isolation membrane and the guide net into 120*120mm sizes (the size can be slightly larger than the size of the carbon fiber woven cloth), and place the release cloth, the perforated isolation membrane and the guide net in order from bottom to top on top of the stacked carbon fiber woven cloth.
[0031] Stick the sealing tape (double-sided tape) around the edges of the mold connection surface to ensure that there are no gaps.
[0032] Cut a vacuum bag slightly larger than the upper surface of the mold, and firmly attach it to the upper surface of the mold through the viscosity of the vacuum tape, leaving two interfaces, and squeeze the bonding area between the vacuum tape and the vacuum bag film to ensure a complete seal.
[0033] Put the mold with the vacuum bag film attached to it into a constant temperature drying oven, connect the two reserved interfaces of the vacuum bag film to two silicone hoses, and lead the silicone hoses out from the vents on the top of the constant temperature drying oven. One of the resin collection tubes is connected to the resin collection interface of the resin collector, and the other resin delivery tube is temporarily clamped and sealed with the first tube clamp. Add a vacuum tube to connect the vacuum extraction interface of the resin collector with the vacuum pump. The function of the resin collector is to collect excess resin to prevent the resin from being sucked into the vacuum pump.
[0034] like Figure 2 As shown, the carbon fiber reinforced composite material sample 9 is covered with a release cloth 85, and the inner side of the vacuum bag film 81 has a guide net 83 and an isolation film 84 from top to bottom, and the connecting surface of the vacuum bag mold 81 and the mold 10 is sealed and connected by a sealing tape 82 to form a vacuum bag.
[0035] Verify the airtightness of the device: turn on the vacuum pump (ultimate vacuum pressure 700mmHg≈0.093Mpa), observe and record the reading of the vacuum gauge after one minute, then clamp the sealing resin collection tube with the second tube clamp and turn off the vacuum pump. Read the reading of the vacuum gauge after 20 minutes. If the readings of the vacuum gauge observed twice are the same (about -0.093Mpa), it proves that the airtightness of the device is good.
[0036] Prepare the curing resin: mix the epoxy resin and curing agent in a weight ratio of 10:3 (make sure the amount of resin is sufficient, which must be greater than twice the weight of the carbon fiber. The total weight of this experiment is 80g), stir thoroughly for two minutes to mix the epoxy resin and curing agent thoroughly, and immerse the resin delivery tube below the liquid level of the curing resin.
[0037] Vacuum induction: Turn on the vacuum pump, the first pipe clamp and the second pipe clamp. The solidified resin will enter the mold through the resin delivery pipe due to the negative pressure and evenly immerse into the carbon fiber filaments of the carbon fiber woven cloth. The excess resin will enter the resin collector through the resin collection pipe. After 90 seconds, close the first pipe clamp and the second pipe clamp in sequence to maintain the vacuum state in the bag, and finally turn off the vacuum pump.
[0038] Heating and curing the resin: Turn on the power of the constant temperature drying oven and raise the temperature to 70°C at a rate of 2°C / min. Set the insulation time to 4h. After the epoxy resin impregnated with the carbon fiber filaments is cured, take it out and demould it when it naturally cools down to 30°C to obtain a carbon fiber reinforced composite material sample.
[0039] refer to Figure 3 As shown, the carbon fiber reinforced composite material sample 9 includes a carbon fiber woven cloth 91, a thermal resistance material 92 and a cured resin; a plurality of carbon fiber woven cloths 91 are stacked as a whole, and a defect space of a set shape is reserved in the middle of one of the carbon fiber woven cloths in the middle layer; the thermal resistance material 92 is filled in the defect space and kept flush with the upper and lower surfaces of the carbon fiber woven cloth, and the cured resin is evenly immersed in the carbon fiber filaments of the carbon fiber woven cloth. The thermal resistance material 92 in this embodiment can be a polytetrafluoroethylene film.
[0040] Calculate the resin content of the sample: weigh and record the carbon fiber reinforced composite material sample (the weight measured in this experiment is 56.72g). Through the weight of the previously weighed carbon fiber woven cloth (37.35g), the material parameters of this sample are obtained: the carbon fiber content is about 65.85%, and the epoxy resin content is about 34.15%.
[0041] Figure 4 This is a thermal map of the sample surface temperature detected by infrared thermal imaging of the sample obtained in Example 1.
[0042] Example 2 (defect depth is about 2.4 mm from the surface): This embodiment is prepared by a vacuum infusion molding process, and the vacuum infusion molding device is referred to Example 1.
[0043] Use non-woven cloth to dip in appropriate amount of alcohol to wipe the stainless steel mold. The size of the groove in the mold is 100*100*4mm, and a 50mm wide connection surface is left on the upper surface; After the alcohol evaporates, spray the inner surface of the mold evenly with an oily release agent; Cut out 26 pieces of 100*100mm bidirectional woven carbon fiber fabrics of the same size (single layer thickness is about 0.15mm), and cut a 20*20mm square hole in the center of one of them, weigh the total weight of the carbon fiber fabric, and record it (the weight of carbon fiber in this experiment is 48.56g); The 26 layers of cut bidirectional woven carbon fiber fabrics are placed in the mold in a circular manner according to the arrangement direction of [0°, 90°, -90°, 0°]. Each layer needs to be evenly sprayed with a shaping spray adhesive to shape it. The 11th layer is laid with a carbon fiber fabric with 20*20mm holes cut out, and a polytetrafluoroethylene film material (20*20mm) of the same size and thickness is filled into the defect to ensure that the film is flush with the upper and lower surfaces of the 11th layer of carbon fiber fabric, and the other layers are arranged normally.
[0044] Cut the release cloth, the perforated isolation membrane and the guide net into 120*120mm sizes (the size can be slightly larger than the size of the carbon fiber woven cloth), and place the release cloth, the perforated isolation membrane and the guide net in order from bottom to top on top of the stacked carbon fiber woven cloth.
[0045] Apply sealing tape to the edges of the mold joint surface to ensure that there are no gaps.
[0046] Cut a vacuum bag slightly larger than the upper surface of the mold, and firmly attach it to the upper surface of the mold through the viscosity of the vacuum tape, leaving two interfaces, and squeeze the bonding area between the sealing tape and the vacuum bag film to ensure a complete seal.
[0047] Put the mold with the vacuum bag film attached to it into a constant temperature drying oven, connect the two reserved interfaces of the vacuum bag film to two silicone hoses, and lead the silicone hoses out from the vents on the top of the constant temperature drying oven. One of the resin collection tubes is connected to the resin collection interface of the resin collector, and the other resin delivery tube is temporarily clamped and sealed with the first tube clamp. Add a vacuum tube to connect the vacuum extraction interface of the resin collector with the vacuum pump. The function of the resin collector is to collect excess resin to prevent the resin from being sucked into the vacuum pump.
[0048] Verify the airtightness of the device: turn on the vacuum pump (ultimate vacuum pressure 700mmHg≈0.093Mpa), observe and record the reading of the vacuum gauge after one minute, then clamp the sealing resin collection tube with the second tube clamp and turn off the vacuum pump. Read the reading of the vacuum gauge after 20 minutes. If the readings of the vacuum gauge observed twice are the same (about -0.093Mpa), it proves that the airtightness of the device is good.
[0049] Prepare the curing resin: mix the epoxy resin and curing agent in a weight ratio of 10:3 (make sure the amount of resin is sufficient, which must be greater than twice the weight of the carbon fiber. The total weight of this experiment is 100g), stir thoroughly for two minutes to mix the epoxy resin and curing agent thoroughly, and immerse the resin delivery tube below the liquid level of the curing resin.
[0050] Vacuum induction: Turn on the vacuum pump, the first pipe clamp and the second pipe clamp. The solidified resin will enter the mold through the resin delivery pipe due to the negative pressure and evenly immerse into the carbon fiber filaments of the carbon fiber woven cloth. The excess resin will enter the resin collector through the resin collection pipe. After 120 seconds, close the first pipe clamp and the second pipe clamp in sequence to maintain the vacuum state in the bag, and finally turn off the vacuum pump.
[0051] Heating and curing the resin: Turn on the power of the constant temperature drying oven and raise the temperature to 70°C at a rate of 2°C / min. Set the holding time to 4 hours. After the epoxy resin impregnating the carbon fiber filaments is cured, naturally cool to about 30°C and remove from the mold to obtain a carbon fiber reinforced composite material sample. The internal structure of the sample can refer to Example 1.
[0052] Calculate the resin content of the sample: weigh and record the carbon fiber reinforced composite material sample (the weight measured in this experiment is 71.26g). Through the weight of the previously weighed carbon fiber woven cloth (48.56g), the material parameters of this sample are obtained: the carbon fiber content is about 68.14%, and the epoxy resin content is about 31.86%.
[0053] Figure 5 This is the sample surface temperature thermal map detected by infrared thermal imaging of the sample in Example 2. Figure 6 This is a three-dimensional graph of the CT results of the sample in Example 2. Figure 7 This is the internal cross-sectional view of the CT results of the sample in Example 2.
[0054] In Example 1 and Example 2, the oily release agent can be 710 oily release agent of Walkerson (Dongguan) New Materials Co., Ltd. The shaping spray glue can be 3M's Super 77 multi-purpose spray glue or Gulchi 998 composite material glue produced by Guangdong Gulchi Aerosol New Energy Technology Co., Ltd. The epoxy resin and curing agent can be GCC135 epoxy resin (M03-A / B epoxy resin glue) and GCC137 curing agent (curing agent 137) produced by Kunshan Jiulimei Electronic Materials Co., Ltd., respectively. This curing resin is a thermosetting epoxy resin resin, and the sample obtained after heating has better performance.
Claims
1. A carbon fiber reinforced composite material structure simulated debonding defect thermal resistance equivalent test piece, characterized in that It comprises carbon fiber woven cloth, thermal resistance material and cured resin; the aforementioned carbon fiber woven cloth is a plurality of pieces which are stacked as a whole, and a defect space of a set shape is reserved in the middle of one of the carbon fiber woven cloths in the middle layer; the thermal resistance material is filled in the defect space and kept flush with the upper and lower surfaces of the carbon fiber woven cloth, and the aforementioned cured resin is evenly immersed in the carbon fiber filaments of the carbon fiber woven cloth.
2. A method for preparing a thermal resistance equivalent test piece of a carbon fiber reinforced composite material structure simulating debonding defects according to claim 1, characterized in that The preparation method adopts a vacuum induction molding device, and the vacuum induction molding device comprises A resin barrel containing curing resin; A resin collector for collecting excess cured resin; A constant temperature drying oven, with a vacuum bag built in, one end of the vacuum bag is connected to the resin barrel through a resin delivery pipe, and the other end is connected to the resin collector through a resin collection pipe, the resin delivery pipe is provided with a first pipe clamp to control the opening and closing of the resin delivery pipe, and the resin collection pipe is provided with a second pipe clamp to control the opening and closing of the resin collection pipe; and A vacuum pump connected to the vacuum end of the resin collector; The steps include: Apply release agent evenly on the inner surface of the mold; The carbon fiber woven cloth is cut to prepare the required number of layers, and a defect space of a set shape is cut out in the middle of one of the carbon fiber woven cloths in the middle layer as a defect layer; Arrange and stack the prepared carbon fiber woven cloth in a certain way in the mold, use shaping spray glue to preliminarily shape it during stacking, fill the defect space with thermal resistance material, and ensure that the top and bottom of the thermal resistance material are flush with the upper and lower surfaces of the carbon fiber woven cloth respectively; Lay the release cloth and the guide net on the upper surface of the stacked carbon fiber woven cloth in sequence; The vacuum bag film is attached to the edge of the upper surface of the mold with a sealing tape and sealed. After the vacuum bag film is wrapped, a vacuum bag is formed. Two interfaces are reserved on the surface of the vacuum bag film for connecting the resin delivery pipe and the resin collection pipe respectively. Turn on the vacuum pump, the first pipe clamp and the second pipe clamp, the solidified resin enters the mold due to the negative pressure and is evenly immersed in the carbon fiber filaments of the carbon fiber woven cloth, and the excess solidified resin enters the resin collector through the resin collection pipe; Close the first tube clamp and the second tube clamp to maintain the vacuum state in the vacuum bag; The carbon fiber filaments are allowed to stand for a while, and after the solidification of the solidifying resin impregnating the carbon fiber filaments is completed, the carbon fiber filaments are taken out and demoulded to obtain a carbon fiber reinforced composite material structure simulating debonding defect thermal resistance equivalent test piece.
3. The preparation method according to claim 2, characterized in that step An isolation film is laid between the demoulding cloth and the guide net.
4. The preparation method according to claim 2, characterized in that step The mold described in the method is made of stainless steel, and the release agent described is an oily release agent.
5. The preparation method according to claim 2, characterized in that step The shaping spray adhesive described in the method is 3M's Super 77 multi-purpose spray adhesive or GURQI 998 composite material adhesive.
6. The preparation method according to claim 2, characterized in that step The curing resin described in the invention comprises the following components and their weight ratios: Epoxy resin 98~102: Curing agent 28~32.
7. The preparation method according to claim 6, characterized in that step The conditions during the static process are as follows: The constant temperature drying oven was controlled to rise to 70°C at a rate of 2°C / min, and the holding time was set to 4h. After the epoxy resin impregnating the carbon fiber filaments was cured, they were naturally cooled to 30°C and then removed from the mold.
8. The preparation method according to claim 2, characterized in that The resin collector is provided with a vacuum gauge, and the steps are as follows: Previously, it also included an airtightness verification step: turn on the vacuum pump for a period of time and then turn it off, and observe the reading of the vacuum gauge to verify the airtightness of the vacuum infusion molding device.
9. The preparation method according to claim 2, characterized in that The vacuum pump is connected to the air extraction end of the resin collector through a vacuum tube.
Citation Information
Patent Citations
Ultrasonic guided wave scanning imaging method for debonding defects in carbon fiber reinforced epoxy resin composite boards
CN102288684A
Vacuum perfusion forming method of p-aramid fiber composite material workpiece
CN102990942A
Liquid molding method of resin-based composite material of interlayer thermoplasticity flow guide net
CN104943200A
Interfacial thermal resistance equivalent specimen of thermal barrier coating structure with simulated debonding defects and preparation method of interfacial thermal resistance equivalent specimen
CN109855939A
Fiber fabric reinforced composite material and preparation method thereof
CN110997290A